1990
DOI: 10.1007/bf00117049
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and growth of a bacterium able to degrade nitrilotriacetic acid under denitrifying conditions

Abstract: A Gram-negative bacterium was isolated from river sediment which was able to grow with nitrilotriacetic acid as a combined carbon, nitrogen and energy source in the absence of molecular oxygen using nitrate as the terminal electron acceptor. Batch growth parameters and mass balances are reported for growth under both aerobic and denitrifying conditions. The strain was characterized with respect to its substrate spectrum and other physiological properties. This denitrifying isolate is serologically unrelated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…This study has shown for the first time that diethanolamine can be degraded without the involvement of molecular oxygen and confirms the finding of Wanner et al (1990) and others that amines can be degraded anaerobically under nitrate reducing conditions. The observation that growth of DEA4 is more rapid under anaerobic conditions than aerobic is unexpected, but might be due to inhibition by oxygen or oxygen metabolites in the aerobic cultures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study has shown for the first time that diethanolamine can be degraded without the involvement of molecular oxygen and confirms the finding of Wanner et al (1990) and others that amines can be degraded anaerobically under nitrate reducing conditions. The observation that growth of DEA4 is more rapid under anaerobic conditions than aerobic is unexpected, but might be due to inhibition by oxygen or oxygen metabolites in the aerobic cultures.…”
Section: Discussionsupporting
confidence: 72%
“…Enfors & Molin 1973 a,b;Egli & Weilenmann 1986). An organism has now been isolated in pure culture which can degrade NTA under denitrifying conditions (Wanner et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore used titanium(II1) as reductant (Zehnder & Wuhrniann, 1976), and we used a modification of the original procedure, with citrate as the anion, involving the less widely utilized nitrilotriacetate (NTA). We have unintentionally confirmed the ease with which anoxic degraders of NTA can be isolated (Wanner et al, 1990), and we foresee a further alteration of the medium to using EDTA, in place of NTA, to try to obtain isolates that are able to utilize the naturally occurring methanesulfonate (Baker et al, 1991), whose degradation in the anaerobic digestor is obviously less common than that of taurine, if it occurs at all.…”
Section: Discussionmentioning
confidence: 96%
“…NTA degradation was shown to be a result of microbial processes rather than of photochemical degradation (1,3,6,17,29,33). Several microorganisms, either obligately aerobic or facultatively denitrifying, that can use NTA as a sole source of carbon, nitrogen, and energy have been isolated (3,10,19,23,30,46,53). The majority of the obligately aerobic isolates has been assigned to two new genera, Chelatobacter and Chelatococcus (2).…”
mentioning
confidence: 99%